Réponses

2013-10-13T19:15:13+02:00
A = (12x²+4x+21x+7)+(10x²+45x+4x+18)=12x²+4x+21x+7+10x²+45x+4x+18=22x²+74x+25
B = (48x²-56x+6x-7)+(20x²+15x-8x-6)=68x²-43x-13
C = (21x²-35x+6x-10)-(30x²+25x-6x-5)=21x²-35x+6x-10-30x²-25x+6x+5=-9x²-48x-5
D = (16x-24-10x²+15x)-(28x-35-4x²+5x)=16x-24-10x²+15x-28x+35+4x²-5x=-6x²-2x+11
2013-10-13T19:47:33+02:00
A = ( 4x + 7 ) ( 3x + 1 ) + ( 5x + 2 ) ( 2x + 9 )
= 4x * 3x + 4x * 1 + 7 * 3x + 7 * 1 + 5x * 2x + 5x * 9 + 2 * 2x + 2 * 9 

= 12x² + 4x + 21x + 7 + 10x² + 45x + 4x + 18
= 22x² + 74x + 25

B = ( 8x + 1 ) ( 6x - 7 ) + ( 5x - 2 ) ( 4x + 3 ) 
= 8x * 6x + 8x * (-7) + 1 * 6x + 1 * (-7) + 5x * 4x + 5x * 3 + (-2) * 4x + (-2) * 3
= 48x² - 56x + 6x - 7 + 20x² + 15x - 8x - 6
= 68x² - 43x - 13

C = ( 7x + 2 ) ( 3x - 5) - ( 5x - 1 ) ( 6x + 5 )
= 7x * 3x + 7x * (-5) + 2 * 3x + 2 * (-5) - 5x * 6x + 5x * 5 + (-1) * 6x + (-1) * 5
= 21x² - 35x + 6x - 10 - 30x² + 25x - 6x - 5 
= -9x² -  48x - 5

D = ( 8 - 5x ) ( 2x - 3 ) ( 7 - x ) ( 4x - 5 )
= 8 * 2x + 8 * (-3) + 5x * 2x + 5x * (-3) + 7 * 4x + 7 * (-5) + (-x) * 4x + (-x) * (-5)
= 16x - 24 - 10x² + 15x -  28x - 35 - 4x² + 5x
= -6x² - 2x + 11